Dental research in the Indian Armed Forces - Vimal Arora; Manu Krishnan (Wolters Kluwer Medknow Publications, 2015)
The Army Dental (AD) Corps is an essential entity under the Indian Army, rendering comprehensive dental care to the combatants and dependents of the Army, Navy, and Air Force. It has a pan-Indian presence, with deployments in all terrains, deep seas, and air spaces in addition to overseas establishments. It delivers high-end clinical services through different levels: Primary dental units, secondary and tertiary dental centers. In addition, it runs some of the finest training schools for dental and paradental professionals. It maintains high standards in clinical practice in all disciplines of dentistry. All these has been made possible largely because of the consistent research pursuits; the corps accomplishes to addresses the clinical requirements and emerging challenges. Research in the AD Corps is done in three modes: (i) Armed Forces Medical Research Committee Projects (AFMRC) done every year by the Indian Army, (ii) Interdisciplinary research among medical and dental specialities, and (iii) Defence Research and Development Organization (DRDO). Through these, it has embarked on advanced, cutting-edge research for new technologies, protocols, and products in the dental sciences. This paper takes stock of current trends in the AD Corps in these domains and highlights its thrust areas toward quality dental treatment.